Phenotypic and Genotypic Resistance of Salmonella Heidelberg Isolated From One of the Largest Poultry Production Region from Colombia - Castro-Vargas, R.; de Rubio, L.C. Fandino; Vega, A.; Rondon-Barragan , I. (International Journal of Poultry Science, 2019)
Background and Objective: Salmonella enterica is a zoonotic pathogen transmitted mainly by consumption of contaminated food from animal origin, especially poultry products. Recently, multidrug resistant Salmonella isolates have been reported as a public health concern, demanding active surveillance. The aim of this study was to analyze both the phenotypic and genotypic antibiotic resistance patterns of Salmonella isolates from healthy chickens in poultry farms of Santander, Colombia. Materials and Methods: Salmonella was isolated from cloacal swabs and characterized by microbiological methods, serotyped and molecularly confirmed by amplification of invA gene. Antibiotic resistance was determined by automated method and agar diffusion method as well as the presence of resistance genes was assessed by PCR. Results: The Salmonella prevalence was 2.8% (15/540) and all isolates were serotyped as Salmonella Heidelberg. All isolates showed phenotypic resistance to 11 out 24 antibiotics evaluated, belonging to quinolones, fluoroquinolones, cephalosporins, β-lactams, aminoglycosides and tetracyclines. Regarding genotypic resistance, all isolates showed the presence of four genes associated with antibiotic resistance, such as strA and strB genes for streptomycin, the gene blaCMY2 that confers resistance to ceftriaxone and the gene sul1 associated with resistance to trimethoprim/sulfamethoxazole. Conclusion: These results indicate that all isolates of Salmonella Heidelberg from poultry farms in Santander, Colombia, are phenotypic and genotypic multiresistant, representing a potential risk to public health. The results also provide information to the resistome present in Salmonella strains from the broiler chicken production chain and update the serotypes present in poultry farms in Colombia.